Annea gen. nov. (Detarieae, Caesalpinioideae, Leguminosae): a home for two species long misplaced in Hymenostegia sensu lato - Mackinder, Barbara A.; Wieringa, Jan J. (Phytotaxa, 2013)
A new genus Annea is described to accommodate two tropical African legume species previously misplaced in Hymenostegia (Leguminosae, Caesalpinioideae, Detarieae). Annea gen. nov. is widespread in tropical Africa but has an unusual disjunct generic distribution, occurring in both upper and lower Guinea but absent from Gabon. Annea afzelii accounts for the generic range in Upper Guinea extending as far east as Equatorial Guinea in the Lower-Guinea region whereas A. laxiflora occupies the southern part of Lower Guinea and shows a preference for drier habitats than the more wide ranging A. afzelii. Hymenostegia dinklagei, a synonym of A. afzelii is neotypified. Neither species of Annea qualifies for a category of threat and both are assessed here as Least Concern (LC) according to IUCN criteria. Scorodophloeus, another exclusively tropical African genus is sister to Annea. Two tables of characters are included, one comparing the morphologies of Annea, Scorodophloeus and Hymenostegia sensu stricto and another providing morphological characters that can be used to separate the two species of Annea. A distribution map of Annea, an illustration of A. afzelii and photographs of A. laxiflora are presented.